RhoA/ROCK Signaling Pathway Mediates Shuanghuanglian Injection-Induced Pseudo-allergic Reactions - Han, Jiayin; Zhao, Yong; Zhang, Yushi; Li, Chunying; Yi, Yan; Pan, Chen; Tian, Jingzhuo; Yang, Yifei; Cui, Hongyu; Wang, Lianmei; Liu, Suyan; Liu, Jing; et al. (Frontiers in Pharmacology, 2018)
Background: Shuanghuanglian injection (SHLI) is a famous Chinese medicine used as an intravenous preparation for the treatment of acute respiratory tract infections. In the recent years, the immediate hypersensitivity reactions induced by SHLI have attracted broad attention. However, the mechanism involved in these reactions has not yet been elucidated. The present study aims to explore the characteristics of the immediate hypersensitivity reactions induced by SHLI and deciphers the role of the RhoA/ROCK signaling pathway in these reactions. Methods: SHLI-immunized mice or naive mice were intravenously injected (iv) with SHLI (600 mg/kg) once, and vascular leakage in the ears was evaluated. Passive cutaneous anaphylaxis test was conducted using sera collected from SHLI-immunized mice. Naive mice were administered (iv) with a single dose of 150, 300, or 600 mg/kg of SHLI, and vascular leakage, histamine release, and histopathological alterations in the ears, lungs, and intestines were tested. In vitro, human umbilical vein endothelial cell (HUVEC) monolayer was incubated with SHLI (0.05, 0.1, or 0.15 mg/mL), and the changes in endothelial permeability and cytoskeleton were observed. Western blot analysis was performed and ROCK inhibitor was employed to investigate the contribution of the RhoA/ROCK signaling pathway in SHLI-induced hypersensitivity reactions, both in HUVECs and in mice. Results: Our results indicate that SHLI was able to cause immediate dose-dependent vascular leakage, edema, and exudates in the ears, lungs, and intestines, and histamine release in mice. These were pseudo-allergic reactions, as SHLI-specific IgE was not elicited during sensitization. In addition, SHLI induced reorganization of actin cytoskeleton and disrupted the endothelial barrier. The administration of SHLI directly activated the RhoA/ROCK signaling pathway both in HUVECs and in the ears, lungs, and intestines of mice. Fasudil hydrochloride, a ROCK inhibitor, ameliorated the SHLI-induced hypersensitivity reactions in both endothelial cells and mice indicating its protective effect. SHLI-induced pseudo-allergic reactions were mediated by the activation of the RhoA/ROCK signaling pathway. Conclusion: This study presents a novel mechanism of SHLI-induced immediate hypersensitivity reactions and suggests a potential therapeutic strategy to prevent the associated adverse reactions.